UNVEILING THE RISE OF MALE DANCERS IN 21ST CENTURY BHARATANATYAM: NAVIGATING CHALLENGES AND SEIZING OPPORTUNITIES - Debnath, Debu; Bhattacharya, Arkadev (ShodhKosh: Journal of Visual and Performing Arts, 2026)
This study examines the factors driving the increasing participation of male dancers in Bharatanatyam, as well as the challenges and opportunities encountered by male dancers in this classical dance form. Through a quantitative analysis of Likert scale responses from 100 respondents, the study explores perceptions of male dancers' impact on Bharatanatyam diversity, the influence of traditional gender roles, the availability of training opportunities, challenges related to societal perceptions, and future prospects. The findings reveal a generally positive perception of male dancers' contributions to Bharatanatyam, alongside persistent challenges associated with traditional gender norms. While improvements in training opportunities offer hope for greater inclusivity, male dancers continue to face unique obstacles in navigating gender expectations.